Rejuvenation of hot mix asphalt incorporating high rap content: issues to consider - Putra Jaya, Ramadhansyah; Z. H., Hussein; Haryati, Yaacob; M. K., Idham; S., Abdulrahman; Choy, L. J. (IOP Science, 2020)
The asphalt used to construct or rehabilitation roads often contains reclaimed asphalt pavement (RAP) in order to diminish not only the use of raw materials but also waste. However, when high level of RAP in hot mix asphalt (HMA) is used, the rejuvenating agents must be employed. A number of aspects must be taken into account to increase pavement service life as much as possible. Thus, the main issues related to the rejuvenation of asphalt mixtures with high levels of RAP are addressed in this paper. In particular, the focal points of this paper will focus on the use of reclaimed asphalt mixtures with maximum efficiency, special attention is paid to how the binder is structured and chemically composes, nature and dose selection of rejuvenator, as well as the diffusion, blending efficiency, homogeneity, time and temperature mixing. A review of the extant and related literature shows that RAP utilization holds promise for the sustainable pavements, provided that some issues were taken into consideration during the designing and application process.